Prove that the equation to

Showing results 1 through 10 of 102,225.
  1. how do i prove the graph of a linear equation is a line? i know the slope between every point should be the same but idk how to
    1. answers icon 4 answers
    2. jubayr asked by jubayr
    3. views icon 622 views
  2. this other one how can i actually prove it if this is the equation to use.the problem states: Prove that if a line has slope ma
    1. answers icon 0 answers
    2. Jasmine20 asked by Jasmine20
    3. views icon 444 views
  3. 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin �y10.Prove that 1+tanθ/1-tanθ = sec^2θ+2tanθ/1-tan^2θ 17.Prove that
    1. answers icon 1 answer
    2. eddy asked by eddy
    3. views icon 678 views
  4. 6. Prove that tan λ cos^2 λ + sin^2λ/sin λ= cos λ� + sin �λ 10. Prove that 1+tanθ/1-tanθ = sec^2θ+2tanθ/1-tan^2θ
    1. answers icon 1 answer
    2. yoshi asked by yoshi
    3. views icon 752 views
  5. Suppose A is a square matrix satisfying the equation A^3 - 2I = 0. Prove that A and (A - I) respectively are invertible. (the
    1. answers icon 1 answer
    2. David asked by David
    3. views icon 794 views
  6. From equation x= A sin wt, prove that the acceleration of SHM is a= -w^2xw is omega actually.. 2.using relationship between
    1. answers icon 1 answer
    2. Syam asked by Syam
    3. views icon 741 views
  7. If the sum of the squares of the roots of the quadratic equation ax^2 + bx + c = 0 is m:n, prove that b^2= 2ac + 4a^2I really
    1. answers icon 1 answer
    2. Jayden Haddy asked by Jayden Haddy
    3. views icon 546 views
  8. My math teacher wants us to prove that all of our answers are correct.But how am I supposed to be able to prove stuff, like
    1. answers icon 4 answers
    2. john asked by john
    3. views icon 667 views
  9. 1. Prove that (f(x+h)-f(x-h))/2=f'(x)2. Prove that any parabola sastifies the equation (f(x+h)-f(x-h))/2=f'(x) For the first
    1. answers icon 1 answer
    2. Andre asked by Andre
    3. views icon 479 views
  10. If cosec A – sin A=a3 , sec A – cos A =b3 , prove thata2 b2 (a2 + b2)=1 Since the first two equations involves two constants
    1. answers icon 0 answers
    2. Manmeet singh asked by Manmeet singh
    3. views icon 793 views